Peningkatan Pemahaman Literasi Digital melalui Pelatihan Aplikasi Website untuk Menentukan Penerima Bantuan Sosial Dana Desa - Muhamad Awiet Wiedanto Prasetyo; Devi Yunita Saputri; Afilda Trisetya Riziana; Ika Romadoni Yunita; Gustin Setyaningsih; Suliswaningsih Suliswaningsih (Institut Ilmu Sosial dan Manajemen Stiami, 2023)
This is reflected in the various development programs that have been shown and intended to provide great concern for efforts to tackle economic problems, because basically the development carried out aims to improve people's welfare. The main requirements for receiving social assistance are being registered by the heads of neighborhood associations and neighborhood associations, loss of livelihood amid the Covid-19 pandemic and not being registered as recipients of other social assistance from the central government which has been described previously. However, when in the field it did not meet the expectations of the community, because it was considered not on target. There needs to be a re-evaluation regarding the assistance program so that it is more targeted because it is not in accordance with the government's previous plans. The solutions offered to overcome the above problems are implementing a website application-based decision support system, Decision Support Systems are not intended to automate decision making, but provide interactive tools that enable decision makers to carry out various analyzes using available models. The method is by coordinating with the village government as a community service partner, the team conducts interviews, observations and documentation to determine problems and appropriate solutions. With training events using the website application as a determination of village fund assistance for the community running smoothly, the obstacle faced is that only the village head and village officials can use the application more optimally, considering that each has a computer and laptop device while the head of the neighborhood association and Not all heads of neighborhood associations have these devices, but they can still use smartphone devices to access them. Comparison of the results of channeling village fund assistance using website application assistance, there are 5 to 11 residents who are not entitled to receive social assistance.